2020
DOI: 10.1108/ilt-07-2020-0260
|View full text |Cite
|
Sign up to set email alerts
|

Experimental dynamic analysis of rod-fastening rotor bearing system with a transverse crack

Abstract: Purpose This study aims to obtain the dynamic behaviours of cracked rod-fastening rotor bearing system (RFBS), and experimental investigation was carried out to examine the dynamic characteristics of this kind of assembled rotor bearing system with a transverse crack passing through the critical speed. Design/methodology/approach An experimental test rig of cracked RFBS was established for examining the vibration behaviours between intact and cracked system. The crack on the surface of a fastening rod was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…e results show that the greater the rotating speed, the greater the influence of rub impact force on the rotor. Wang et al [14,15] studied the influence of coupling faults such as uneven contact stress distribution between two disk and initial bending of the system due to the existence of cracks on rotor dynamic characteristics and verified it through experiment. Cui et al [16] used finite element method to study the dynamic characteristics of rod fastening rotor under different preload and bearing assembly clearance.…”
Section: Introductionmentioning
confidence: 99%
“…e results show that the greater the rotating speed, the greater the influence of rub impact force on the rotor. Wang et al [14,15] studied the influence of coupling faults such as uneven contact stress distribution between two disk and initial bending of the system due to the existence of cracks on rotor dynamic characteristics and verified it through experiment. Cui et al [16] used finite element method to study the dynamic characteristics of rod fastening rotor under different preload and bearing assembly clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [27] studied the nonlinear dynamic characteristics of a three-disk bending torsional coupling rod fastening rotor under rub impact fault, concluded that the influence of torsional vibration on bending vibration gradually increases with the increase in rotating speed. Wang et al [28,29] studied the dynamic characteristics of rod fastening rotor under the coupling fault state, which are the non-uniform contact stressors of the disks, crack, initial bending and others, and carried out experimental verification. Hei et al [30,31] studied the nonlinear dynamic characteristics of coupling faults, which are the rod fastening rotor with looseness of support and rub impact.…”
Section: Introductionmentioning
confidence: 99%